COMPARISON OF REVENUE FROM MOUNT KELUD TOURIST ATTRACTION LEVIES AND REGIONAL ORIGINAL INCOME IN KEDIRI REGENCY - Anggraini, Ninik; Wahyudi, Moch (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 4 No 01 (2024): AMMER: ISSUE MAY 2024DO - 10.32503/ammer.v4i01.5769, 2024)
The issue in this study is to examine whether there are differences in the revenue from tourist attraction levies at Mount Kelud and the revenue from the regional original income through financial report analysis, which will use data from the tourism sector levies, specifically the Mount Kelud tourist attraction and the regional original income of Kediri Regency, over a period of 5 years before and 3 years after the occurrence of Covid-19. The population of this study is all annual financial reports issued by the DISPARBUD (Department of Tourism and Culture) of Kediri Regency. The financial reports of Mount Kelud tourism levies and the regional original income over 8 periods are divided into 5 periods before Covid-19 and 3 periods after Covid-19, from the years 2015/2018 to 2022/2023. The analytical technique used in this study is a comparative quantitative method through the Paired Sample t-test analysis approach. The results of this study show that the tourism levies before the occurrence of Covid-19 differ significantly from the tourism levies after the occurrence of Covid-19. It is evident that the t-value is 2.251 with a probability value of 0.039, which is less than the 0.05 threshold. The regional original income of Kediri Regency before the occurrence of Covid-19 also differs significantly from the regional original income after the occurrence of Covid-19. It is evident that the t-value is 2.955 with a probability value of 0.042, which is less than the 0.05 threshold.